Tính nhanh
\(\left(19^{20}+19^{19}\right):19^{18}=\)
\(\left(8^{2018}+8^{2019}\right):8^{2019}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Chúc mày học ngu
Chúc mày học ngu
Chúc mày học ngu
Chúc mày học ngu
\(\left(\frac{19}{2018}-2019\right).\frac{1}{2019}-\left(\frac{1}{2018}-2019\right).\frac{19}{2019}\)
\(=\frac{19}{2018}-2019.\frac{1}{2019}-\frac{-1}{2018}+2019.\frac{19}{2019}\)
\(=\left(\frac{19}{2018}-\frac{-1}{2018}\right)-\left(2019+2019\right).\left(\frac{1}{2019}.\frac{19}{2019}\right)\)
\(=\frac{18}{2018}-2038.\frac{19}{2019}\)
còn đâu tự tính nha
Đặt \(\left\{{}\begin{matrix}2018-x=a\\x-2019=b\end{matrix}\right.\) \(\Rightarrow a+b=-1\Rightarrow b=-1-a\)
\(\frac{a^2+ab+b^2}{a^2-ab+b^2}=\frac{19}{49}\Leftrightarrow49\left(a^2+ab+b^2\right)=19\left(a^2-ab+b^2\right)\)
\(\Leftrightarrow15a^2+34ab+15b^2=0\)
\(\Leftrightarrow\left(5a+3b\right)\left(3a+5b\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}5a=-3b\\3a=-5b\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}5a=-3\left(-1-a\right)\\3a=-5\left(-1-a\right)\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}2a=3\\2a=-5\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}a=\frac{3}{2}\\a=-\frac{5}{2}\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}2018-x=\frac{3}{2}\\2018-x=-\frac{5}{2}\end{matrix}\right.\) \(\Rightarrow\left[{}\begin{matrix}x=\frac{4033}{2}\\x=\frac{4041}{2}\end{matrix}\right.\)
\(a,=\left(\frac{9}{16}-\frac{10}{16}+\frac{12}{16}\right):\frac{11}{32}\)
\(=\frac{11}{16}:\frac{11}{32}\)
\(=\frac{11}{16}.\frac{32}{11}\)
\(=2\)
\(=-19-40+19+\left(-3\right)\cdot\left(-8\right)\)
\(=-40+24=-16\)
7)\(\dfrac{-19}{34}\left(\dfrac{17}{19}+\dfrac{49}{18}\right)+\dfrac{49}{18}\left(\dfrac{19}{34}-\dfrac{18}{7}\right)\)
=\(\dfrac{-19}{34}.\dfrac{17}{19}+\dfrac{49}{18}.\dfrac{-19}{34}+\dfrac{49}{18}.\dfrac{19}{34}-\dfrac{18}{7}.\dfrac{49}{18}\)
=\(\dfrac{1}{2}+\left(\dfrac{49}{18}.\dfrac{-19}{34}+\dfrac{49}{18}.\dfrac{19}{34}\right)-7\)
=\(\dfrac{1}{2}+\left[\dfrac{49}{18}\left(\dfrac{-19}{34}+\dfrac{19}{34}\right)\right]-7\)
=\(\dfrac{1}{2}+0-7=\dfrac{-13}{2}\)
8)\(\dfrac{29}{32}\left(\dfrac{41}{36}-\dfrac{32}{58}\right)-\dfrac{41}{36}\left(\dfrac{29}{32}+\dfrac{18}{41}\right)\)
=\(\dfrac{29}{32}.\dfrac{41}{36}-\dfrac{29}{32}.\dfrac{32}{58}-\dfrac{41}{36}.\dfrac{29}{32}+\dfrac{18}{41}.\dfrac{41}{36}\)
=\(\left(\dfrac{29}{32}.\dfrac{41}{36}-\dfrac{41}{36}\dfrac{29}{32}\right)-\dfrac{29}{32}.\dfrac{32}{58}+\dfrac{18}{41}.\dfrac{41}{36}\)
=\(0-\dfrac{1}{2}+\dfrac{1}{2}=0\)
Ta có: \(\left(-19\right)+5+\left(-8\right)+19+\left(-3\right)\cdot\left(-2\right)^3\)
\(=\left(-19+19\right)+\left(5-8\right)+\left(-3\right)\cdot\left(-8\right)\)
\(=-3+24=21\)
\(1\frac{13}{15}\cdot\left(0,5\right)^2\cdot3-\left(\frac{8}{15}+1\frac{19}{60}\right):1\frac{19}{60}\)
\(=\frac{28}{15}\cdot\frac{1}{4}\cdot\frac{3}{1}-\frac{37}{20}\cdot\frac{60}{79}\)
\(=\frac{7}{5}-\frac{111}{79}\)
\(=\frac{-2}{395}\)
=28/15.1/4.3-8/15-79/60.60/79
=7.4/15.1/4.3-8/15-1
=7/15.3-8/15-1
=21/15-8/15-1
=13/15-1
=-2/15
\(\left(19^{20}+19^{19}\right):19^{18}\)
\(=19^{20}:19^{18}+19^{19}:19^{18}\)
\(=19^2+19=19\left(19+1\right)=380\)
+) \(\left(8^{2018}+8^{2019}\right):8^{2019}\)
\(=8^{-1}+8^1=\dfrac{65}{8}\)